Ganoderma lucidum spore extract improves sleep disturbances in a rat model of sporadic Alzheimer’s disease - Qin, Yu; Zhao, Yan; Hu, Xiao; Chen, Xi; Jiang, Yan-Ping; Jin, Xue-Jun; Li, Gao; Li, Zhen-Hao; Yang, Ji-Hong; Zhang, Guo-Liang; Cui, Su-Ying; Zhang, Yong-He (Frontiers in Pharmacology, 2024)
Introduction:Ganoderma lucidum (G. lucidum, Lingzhi) has long been listed as a premium tonic that can be used to improve restlessness, insomnia, and forgetfulness. We previously reported that a rat model of sporadic Alzheimer’s disease (sAD) that was induced by an intracerebroventricular injection of streptozotocin (ICV-STZ) showed significant learning and cognitive deficits and sleep disturbances. Treatment with a G. lucidum spore extract with the sporoderm removed (RGLS) prevented learning and memory impairments in sAD model rats. Method: The present study was conducted to further elucidate the preventive action of RGLS on sleep disturbances in sAD rats by EEG analysis, immunofluorescence staining, HPLC-MS/MS and Western blot. Results: Treatment with 720 mg/kg RGLS for 14 days significantly improved the reduction of total sleep time, rapid eye movement (REM) sleep time, and non-REM sleep time in sAD rats. The novelty recognition experiment further confirmed that RGLS prevented cognitive impairments in sAD rats. We also found that RGLS inhibited the nuclear factor-κB (NF-κB)/Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammatory pathway in the medial prefrontal cortex (mPFC) in sAD rats and ameliorated the lower activity of γ-aminobutyric acid (GABA)-ergic neurons in the parabrachial nucleus (PBN). Discussion: These results suggest that inhibiting the neuroinflammatory response in the mPFC may be a mechanism by which RGLS improves cognitive impairment. Additionally, improvements in PBN-GABAergic activity and the suppression of neuroinflammation in the mPFC in sAD rats might be a critical pathway to explain the preventive effects of RGLS on sleep disturbances in sAD.